WHAT MONGOLIA PRODUCES THAT THE WORLD SHOULD KNOW ABOUT? CONSUMERS’ INFORMATION PROCESSING MECHANISMS - PUREVDORJ, Tuul; SILVA, Susana Costa e (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
The present study attempts to understand the use of three information processing mechanisms – cognitive, affective, and normative – to assess the quality of cashmere products made in Mongolia. For attaining the above aims, semi-structured interviews were conducted to test a framework that resulted from literature reviewed on country of origin (COO) effect and information processing mechanisms. Results demonstrate that for Business-to-Business (B2B) clients, the COO is an extremely relevant cue to evaluate the quality of cashmere. Conversely, most of the consumers do not seem to include the COO effect on their information processing and base their evaluation on four distinct product-related attributes: quality, brand, social status, and price. Results are relevant for the Mongolian cashmere industry, as well as for marketers interested in understanding what drives consumers of cashmere in their buying decisions. We also understand these findings to assist in improving the image of Mongolia as one of the world’s best manufacturers of cashmere. JEL classification: M31, M38